EMOTIONAL INTELLIGENCE AND ACADEMIC SUCCESS: RETHINKING SOCIO-EMOTIONAL LEARNING IN DIGITAL CLASSROOMS - Sofia F Rahmani; Rinda Riztya; Jeprianto Jeprianto (Adisam Publisher, 2025)
The transformation of education toward a digital ecosystem has brought significant changes to the dynamics of learning, social interactions, and emotional well-being of students. In this context, emotional intelligence is a crucial factor in determining academic success, especially amidst the increasing reliance on distance learning technology. This study, titled